The relationship between verb meaning and argument realization: What we learn from the processing of agent-implying intransitive verbs in Japanese - Luk, Zoe Pei-sui (Frontiers in Psychology, 2022)
This study investigated whether some Japanese intransitive verbs, called agent-implying intransitive verbs, are processed differently from other ordinary intransitive verbs. These verbs are special in that they denote agentive events, but they are intransitive verbs, which only allow the patient/theme to be the only nominatively marked argument. The priming experiment was designed based on the situation model theory, assuming that verbs with an agentive semantic structure (e.g. ordinary transitive verbs) has a shorter causal inferential distance than those with a non-agentive semantic structure (e.g. ordinary intransitive verb). In the experiment, participants were instructed to read two sentences that formed a story, of which the second sentence was either a transitive or intransitive sentence. The participants then answered a related question about general knowledge, and their response times were measured. The results show that, whereas the mean response time in the ordinary intransitive condition was significantly longer than that in the ordinary transitive condition, the mean response time in the agent-implying intransitive condition was not significantly different from that of the corresponding transitive condition, suggesting that agent-implying intransitive verbs are interpreted as agentive. The findings suggest that agent-implying intransitive verbs instantly evoke agentivity, whereas ordinary intransitive verbs do not. The theoretical implications of the findings are discussed.